Methodological challenges in Health research during and aftermath of COVID-19 pandemic era - Srijana Bhattarai; Shalabh Shah; Bhanu Bhakta Bashyal; Chandra Bahadur Sunar; Kaushalya Shrestha (Journal of Nepal Medical Association, 2025)
The global pandemic of COVID-19 has had an impact on health, social and economic sectors. Health research is not exempt from the current crisis and is facing many challenges. The main challenges while conducting health research in the COVID-19 context include methodological challenges faced during data collection’, ‘difficulty in identifying non-verbal cues’, ‘time constraints’ and ‘ethical issues. Responding to the crisis, quantitative and qualitative research projects need some modifications to address the challenges of conducting research in the COVID-19 pandemic context. This commentary highlights the major challenges encountered while conducting research during the COVID-19 pandemic and provides ways quality research can be conducted in pandemic or other situations where physical distancing needs to be maintained.